HUBUNGAN KUALITAS TIDUR DENGAN SIKLUS MENSTRUASI SISWI SMAN 1 TALANG KELAPA KABUPATEN BANYUASIN (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
Menstruation is regular bleeding from the uterus as a sign that the uterine organs are functioning properly. If a woman does not experience pregnancy, the menstrual cycle will occur every month. Although menstruation is a natural process experienced by women, it is a major problem in society if menstrual disorders occur. This disorder may be related to the length of the menstrual cycle or the number and duration of menstruation. Another disturbance that can occur during menstruation is a disturbance in sleep patterns. The sleep pattern that most people go through is sleeping for several hours at a time, ages 12-18 years before adolescence to adolescents the need for healthy sleep is 8-19 hours, studies show that adolescents who are sleep deprived are more prone to depression, do not focus and have poor school grades. This study aims to determine the relationship between sleep quality and menstrual cycle. The research was conducted at SMAN 1 Talang Kelapa Banyuasin from November to December 2020 with a research sample of 42 people who were taken through stratified random sampling. This research is an analytic observational study with a cross-sectional design and tested using chi-square analysis. The results showed that there was no relationship between sleep quality and menstrual cycle with a p-value = 1,000. It was suggested for SMAN1 Talang Kelapa to form PIK-KRR so that it could help students' problems in the field of reproductive health.